Penggunaan Model Cooperative Script Terhadap Kemampuan Pemahaman dan Komunikasi Matematis Siswa - Rusdian Rifa'i (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
This study is a quasi-experimental study designed control group of non-equivalent that aims to investigate the effect of cooperative script learning model use on the students’ ability of mathematical understanding and communication. The sample of this study is class X AP 1 and class X AP 2 students. The instruments used in this study are: understanding ability test, mathematical communication test, and the student attitude scale. The findings and data analysis show: There is an interaction between cooperative script learning model and conventional learning with MEA of students are capable of high, medium and low towards the increase of students’ mathematical communication, there is a relationship between understanding ability and mathematical communication of students, and students respond positively on cooperative script learning model in learning mathematics.